Seleção de colônias de Clostridium perfringens tipo D produtoras de toxina épsilon por "dot blot" - Luciana Aramuni Goncalves (2004)
In order to select strains of Clostridium perfringens type D producers for epsilon toxin, a dot blot was standardized test using epsilon toxin adsorbed in nitrocellulose membrane, anti-epsilon toxin produced in sheep and anti-immunoglobulin of sheep produced in rabbit conjugated with peroxidase. The reaction was visualized using DAB Substrate Kit 3,3 diaminobenzidine and the reading was made according to the intensity of color obtained in each well. Clones producing epsilon toxin were selected by limiting dilution and after three passages, mortal minimum dose (MMD) titres were determined in mice. Selected clones produced epsilon toxin 1000 times more concentrated those the original strain. The presence of the gene etx that encodes the synthesis of the epsilon toxin was verified by the polymerase chain reaction, and all clones were positive, including those negative at the dot blot. It was concluded that the dot blot test was efficient for selecting toxigenic colonies of C. perfringens type D.